2011
DOI: 10.1007/s10742-011-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Genes as instruments for studying risk behavior effects: an application to maternal smoking and orofacial clefts

Abstract: This study uses instrumental variable (IV) models with genetic instruments to assess the effects of maternal smoking on the child’s risk of orofacial clefts (OFC), a common birth defect. The study uses genotypic variants in neurotransmitter and detoxification genes relateded to smoking as instruments for cigarette smoking before and during pregnancy. Conditional maximum likelihood and two-stage IV probit models are used to estimate the IV model. The data are from a population-level sample of affected and unaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 101 publications
1
32
0
Order By: Relevance
“…Other confounders such as maternal use of medications during pregnancy may also be at play. To further check for confounding, we estimated a model adding maternal smoking during pregnancy, a well-known risk factor for oral clefts and child development, as a covariate in addition to a dummy variable to indicate observations with missing data on smoking (∼40%) to retain the full sample 34 35. We found the same results as those in table 2 (see online supplementary table S1).…”
Section: Discussionmentioning
confidence: 63%
“…Other confounders such as maternal use of medications during pregnancy may also be at play. To further check for confounding, we estimated a model adding maternal smoking during pregnancy, a well-known risk factor for oral clefts and child development, as a covariate in addition to a dummy variable to indicate observations with missing data on smoking (∼40%) to retain the full sample 34 35. We found the same results as those in table 2 (see online supplementary table S1).…”
Section: Discussionmentioning
confidence: 63%
“…26,35 The pups exposed to nicotine had statistically significant LBW and shorter body length as compared to control group, confirming the momentous negative impact of maternal nicotine exposure on the size of the offspring. Additionally, frequency of stillborn pups was considerably higher in nicotine-treated dams, thus showing the deleterious effect of nicotine on the developing fetus.…”
Section: Discussionmentioning
confidence: 59%
“…25 Meanwhile, polymorphisms of several genes, including MSX1, TGFB3, BCL3, CYP1A1, GSTP1, and GSTT1 have been examined in conjunction with maternal alcohol consumption, cigarette smoking, medication use, and multivitamin supplementation during pregnancy. [25][26][27] It was shown that smoking by both parents interacts with a specific allelic variant of MSX1, which significantly increase the OFC risk for their offspring. 28 Moreover, a novel approach was developed by Wehby et al 26 to study the role of maternal smoking and OFC, in which they found out that smoking before and during pregnancy increased the risk of OFC by about 4-5 times at the sample average smoking rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk factors have been associated with a variety of adverse infant and child health outcomes and conditions including mortality, low birth weight (LBW), birth defects, asthma, obesity, and developmental delays/problems [14]. …”
mentioning
confidence: 99%